Green parties and building permissions: Evidence from Bavarian municipalities - Patrick Hufschmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper studies whether the rise of environmental parties during the last few decades can provide an explanation for reduced housing supply. Specifically, we examine the impact of Green Party presence on short-term housing supply in Bavarian municipalities from 1987 to 2019. Using a set of staggered difference-in-differences approaches and a large panel data set, we find that the entry of Green Party members into municipal councils leads to an approximate 5.6% decrease in the short-term issuance of building permits. Our results suggest that even in minority positions, Green Party members can influence local decision-making through highlighting the negative externalities associated with construction projects. Moreover, this influence may lead to policy convergence, where other parties adopt some elements of the Green Party's environmental agenda to appeal to environmentally conscious voters. Overall, our study contributes to understanding the trade-offs between housing supply and environmental protection in decentralized democratic settings and sheds light on the role of Green Party members in shaping local land use policy. – – Dieses Papier untersucht, ob der Aufstieg von Umweltparteien in den letzten Jahrzehnten eine Erklärung für reduzierte Wohnraumversorgung bieten kann. Insbesondere werden die Auswirkungen der Präsenz der Grünen auf die kurzfristige Wohnraumversorgung in bayerischen Gemeinden von 1987 bis 2019 analysiert. Unter Verwendung eines Satzes von gestaffelten Differenz-in-Differenzen-Ansätzen und eines großen Paneldatensatzes zeigt sich, dass der Eintritt von Mitgliedern der Grünen in die Gemeinderäte zu einem ungefähren Rückgang der kurzfristigen Erteilung von Baugenehmigungen um 5,6 Prozent führt. Die Ergebnisse deuten darauf hin, dass Mitglieder der Grünen auch in Minderheitspositionen die lokale Entscheidungsfindung beeinflussen können, indem sie die negativen Externalitäten hervorheben, die mit Bauvorhaben verbunden sind. Darüber hinaus kann dieser Einfluss zu einer Politikkonvergenz führen, bei der andere Parteien einige Elemente der umweltpolitischen Agenda der Grünen übernehmen, um umweltbewusste Wähler anzusprechen. Insgesamt trägt diese Studie zum Verständnis der Abwägungen zwischen Wohnraumversorgung und Umweltschutz in dezentralisierten demokratischen Systemen bei und beleuchtet die Rolle von Mitgliedern von Umweltparteien bei der Gestaltung der lokalen Flächennutzung.
Keywords: H73; H77; R31; R38; Q56; 330; Party effects; housing supply; land use policies; natural resources; difference-indifferences